Comparison of Fenton and Fered-Fenton processes for sustainable management of textile reverse osmosis concentrate: multivariate analysis approach - Canbakal, Gamze; Ersoz, Oykue Nur; Cene, Gulay Arslan; Guvenc, Senem Yazici; Can-Guven, Emine; Varank, Gamze (WILEY, 2025)
BackgroundWater scarcity and increasingly stringent discharge regulations are driving the adoption of sustainable water management strategies, necessitating the reuse of industrial wastewater and the implementation of zero or near-zero liquid discharge systems. Reverse osmosis (RO) is an effective technology for recycling wastewater in the textile industry. The elevated resistivity and decreased biodegradability of contaminants in RO concentrates generate a novel wastewater stream.ResultsThis study examines the reutilization of these wastewaters through Fenton and Fered-Fenton processes. The Box-Behnken design (BBD) was used to model process variables. The operational parameters for both processes were the H2O2/chemical oxygen demand (COD) ratio, Fe2+/H2O2 ratio, current density and reaction time. The evaluated system responses were COD, color index (CI) and ultraviolet absorbance at 254 nm (UV254) and 280 nm (UV280). The correlation coefficients (R2) for all created models approached 1, demonstrating the efficacy of the BBD method in modeling pollutant removal with the Fenton and Fered-Fenton processes. The Fenton process achieved removal efficiency of 73.5% for COD, 94.5% for CI, 84% for UV254 and 81% for UV280. The efficiencies obtained in the Fered-Fenton process were 87% for COD, 97.5% for CI, 94.5% for UV254 and 89% for UV280 under optimum conditions.ConclusionsThe results indicate that the modified Fenton process may be a more successful alternative method, notably owing to its enhanced removal efficiencies for organic matter. (c) 2025 Society of Chemical Industry (SCI).
Keywords: color index; Fenton; response surface methodology; reverse osmosis concentrate; textile wastewater treatment; WASTE-WATER TREATMENT; ELECTROCHEMICAL ADVANCED OXIDATION; ELECTRO-FENTON; PEROXI-COAGULATION; LANDFILL LEACHATE; DEGRADATION; REMOVAL; EFFLUENT; H2O2; ELECTROOXIDATION; Biotechnology & Applied Microbiology; Chemistry; Engineering